Carbonatação de pastas cimentícias petrolíferas modificadas com polímero estireno butadieno, sílica cristalina e sílica ativa - Nascimento, Jonathan Dias (2019)
This work aimed to study the effect of the exposition of Portland class G cement slurries, intended to oil wells, to carbon dioxide (CO2) in water-saturation. Four different systems of slurry with total water/ solid material (wt/sm) of 0.33 ± 0.01 density of 1.98 ± 0.06 g/cm3 were selected. The first cementitious system was a reference Portland class G cement slurry commonly used for the cementation of wells (PR). The other systems were obtained modifying the reference slurry with the partial cement replacement by styrene-butadiene copolymer latex (PR+L), silica fume (PR+SA) or crystalline silica (PR+S). The slurries were optimized in order to fulfill the reological, physical and mechanical requirements to the cementation of oilfields. The optimization of the slurries was performed by of consistometry, rheology, free fluid, filtrate, static sedimentation, indirect compression strength by the ultrasonic method and acoustic impedance. After 14 days of cure under pressure and temperature (55 MPa and 65 °C, respectively), the cement slurries samples were placed in carbonation chambers and submitted CO2 environment at 65 °C and 21 MPa pressure, for 30, 60 and 90 days. The carbonation in function of the time of CO2 exposure was analyzed through thermogravimetric analysis, x-ray diffractometry, optical microscopy, CO2 gasometry, total porosity, gas permeability, uniaxial compression strength and Brazilian tensile test. The profile carbonation along the diameter of the cylindrical samples was also evaluated by thermogravimetric analysis. From the results obtained, it was observed that reducing the amount of carbonationable material in the cement slurries was not sufficient to avoid carbonation. The porosity and permeability to CO2 and the microstructural arrangement are determining factors for the advance of carbonation.